1878 Miss. Laws 175, ch.46 § 1 - (:unkn) unknown (General Publisher, 1878)
Prohibited the carrying of a concealed Bowie knife, pistol, brass knuckles, slungshot or other deadly weapon. Excepted travels other than “a tramp.” Punishable by fine of $5-100.
--
Keywords: CARRY - CONCEALED